Development of a compassion-focused and contextual behavioural environment and validation of the Therapeutic Environment Scales (TESS). (February 2016) - Veale, David; Miles, Sarah; Naismith, Iona; Pieta, Maria; Gilbert, Paul
Abstract : Aims and method: The aims of the study were to develop a scale sensitive enough to measure the interpersonal processes within a therapeutic environment, and to explore whether the new scale was sensitive enough to detect differences between settings, including a community based on compassionate mind and contextual behaviourism. The Therapeutic Environment Scales (TESS) were validated with 81 participants in three different settings: a specialist service for anxiety disorders, a specialist in-patient ward and a psychodynamic therapeutic community. Results: TESS was found to be reliable and valid. Significant differences were seen between the services on the dimensions of compassion, belongingness, feeling safe, positive reinforcement of members' acts of courage, extinction and accommodation of unhelpful behaviours, inconsistency and high expressed emotion. These processes were over time associated with improved outcomes on a specialist service for anxiety disorders. Clinical implications: The TESS offers a first step in exploring important interpersonal relationships in therapeutic environments and communities. An environment based on a compassionate mind and contextual behaviourism offers promise for the running of a therapeutic community.